EXPERIMENTAL DETERMINATION OF THE OXYGEN TRANSFER COEFFICIENT (kLa) IN A BATCH BIOREACTOR - Erazo E., Raymundo (2001)
The volumetrlc oxygen transfer coefficient, kLa, has been determined experimentally in a batch operating bioreactor at 30ºC. It was found that it is dlrectly proportional to the degree of aereation and the agitation, whlie it is inversely proportional to the viscosity. This behavior is in accord with other correlations found in the literature [3, 7]. The gas eliminatlon method may be applied to systems with or without presence of microorganisms. As a result the only required data are the concentrations of dissolved oxygen as a function of time.